Enhanced visible-light photocatalytic performance of BiOBr/UiO-66(Zr) composite for dye degradation with the assistance of UiO-661. Issue 49 (30th May 2015) - Sha, Zhou; Wu, Jishan
<x xml:space="preserve">Abstract</x> A BiOBr/UiO-66(Zr) composite was used as visible-light promoted photocatalyst for the degradation of rhodamine B with high activity and good catalyst stability.